Об одной системе алгебраических уравнений - Белов, И. С. (НТУ "ХПИ", 2010)
Розглянуто систему алгебраїчних рівнянь другого порядку, що виникає в теорії невід’ємних тригонометричних многочленів. Подані умови збіжності деяких лінійних функцій від розбіжних ітерацій метода Ньютона рішення цієї системи.

The system of the algebraic equations of the second order, arising in the theory of nonnegative trigonometrical polynominals is considered. Conditions of convergence of some linear functions from iterations of Newtons method of the decision of this system are given.
Keywords: итерационные методы решения; метод Ньютона; свойства неотрицательных тригонометрических многочленов; уравнения второго порядка; теория неотъемлемых тригонометрических многочленов